Evaluasi sistem dan prosedur pengeluaran kas di Badan Pengembangan Sumber Daya Manusia Daerah (BPSDMD) Provinsi Sulawesi Utara - Sambur , Michelle Yubilia Maria; Manossoh , Hendrik; Afandi , Dhullo (Yayasan Widyantara Nawasena Raharja, 2024)
Accounting systems and procedures of SKPD cover various processes ranging from recording, summarizing and financial reporting in the framework of APBD accountability. Cash is a current asset and in everyday monetary terms can be equated with cash on hand. The purpose of this study is to find out the systems and procedures for disbursing cash by implementing PERMENDAGRI Number 77 of 2020 at the Regional Human Resources Development Agency (BPSDMD) of North Sulawesi Province. The results of the study show that the internal control system for disbursing cash at the BPSDMD of North Sulawesi Province according to the Government Regulation Number 60 of 2008 is good, but there are still 3 points that are not appropriate, namely the control environment, control activities, information and communication. Procedures for disbursing cash at the BPSDMD of North Sulawesi Province are not fully implemented accordance to Permendagri No. 77 of 2020.